Research progress on the applications of electrospun nano-fibers in catalysis. - Guerrero-Pérez, María Olga (MDPI, 2021)
During the last two decades, electrospinning has become a very popular technique for the fabrication of nanofibers due to its low cost and simple handling. Nanofiber materials have found utilization in many areas such as medicine, sensors, batteries, etc. In catalysis, these materials also present important advantages, since they present a low resistance to internal diffusion and a high surface area to volume ratio. These advantages are mainly due to the diameter–length proportion. A bibliographic analysis on the applications of electrospun nanofibers in catalysis shows that there are two important groups of catalysts that are being investigated, based on TiO2 and in carbon materials. The main applications found are in photo- and in electro-catalysis. The present study contributes by reviewing these catalytic applications of electrospun nanofibers and demonstrating that they are promising materials as catalysts, underlining some works to prove the advantages and possibilities that these materials have as catalysts. On one hand, the possibilities of synthesis are almost infinite, since with coaxial electrospinning quite complex nanofibers with different layers can be prepared. On the other hand, the diameter and other properties can be controlled by monitoring the applied voltage and other parameters during the synthesis, being quite reproducible procedures. The main advantages of these materials can be grouped in two: one related to their morphology, as has been commented, relative to their low resistance and internal diffusion, that is, their fluidynamic behavior in the reactor; the second group involves advantages related to the fact that the active phases can be nanoscaled and dispersed, improving the activity and selectivity in comparison with conventional catalytic materials with the same chemical composition.
Keywords: Catálisis; Fibras; Nanoestructuras; Catalysis; Electrospun nanofibers